Study on Assessment and Feasibility of Hythane From POME to Improve Power Plant Performance - Era Restu Finalis; Joni Prasetyo; Galuh Wirama Murti; SD Sumbogo Murti; Nesha Adelia (Majalah Ilmiah Pengkajian Industri, 2022)
Biogas power plant from POME is getting trendier because Indonesia is the largest palm oil producer in the world as the amount of palm oil production produces more POME and has a high COD. COD is commonly used as a base stoichiometry calculation for CH4 conversion. Correction on COD conversion for biogas production was done by considering CO2 rather than CH4 only. Combining H2 with CH4 is a worthy breakthrough because it can increase by 15% of electricity output. Such H2 and CH4 mixing has some advantages on the unique combustion property of H2 in CH4 (hythane). Economic analysis comparison on this mixing of biogas and conventional biogas was assessed to see the improvement because of an increase in LHV value in biogas. Based on previous experiments conducted by cascading H2 and followed by CH4 production, with an H2 in CH4 ratio of 1:3, an economic analysis was calculated according to an industry capacity of 60 tonnes FFB/hour. A previous biogas power plant needed an investment of $1,502,000 for 1.35 MWe, but $400,000 was later invested for 1.59 MWe by hythane, increasing 15%. The investment performance of this power plant gave IRR 43.96%, 9.95% higher, and low BEP, 34%. The biogas power plant is economically safe, does not suffer from losses even produces only 34% capacity. The payback period was 2.6 years, seven months shorter. In conclusion, an additional one bioreactor on the existing power plant is economically feasible. Keyword: POME (Palm Oil Mill Effluent), Hythane, Hydrogen Methane, Economic Analysis, Cascading Fermentation.